Preparation and characterization of polyvinyl chloride (PVC)/ reclaimed butadiene rubber (rNBR) - Ee, Yu Feng (2024)

(untitled)
Recycling of waste nitrile butadiene rubber is very hard to implement due to its threedimensional crosslink network, which exists between NBR chains. This threedimensional network is hard to be cleavage and break down. NBR with crosslinks cannot be re-compounded, cannot flow and re-molded into new products. Thus, the recycling and end of life use of NBR waste are limited to grinding it to powder to be used as filler material or through pyrolysis, respectively. Bridge Fields Resources Group (BFR) started their research with Universiti Tunku Abdul Rahman (UTAR) from 2012 to develop a new technique to reclaimed NBR (rNBR). The developed technology is used to devulcanize NBR using plant-based chemicals at room temperature and pressure using existing rubber processing equipment. The rNBR could be re-compounded, flow and re-molded into an entirely new product. In this project, the rNBR will be blended with plasticized PVC in various compositions (100/0, 90/10, 80/20, 70/30, 60/40, 50/50) and its properties will be studied. The properties will be compared with standard specification requirement given for anti-slip bathroom mat product by CY Handee Rubber Moulding Sdn. Bhd. Minimum specifications needed for an anti-slip bathroom mat application include ultimate tensile strength of 5 MPa, 25% of elongation at break with a maximum water absorption of 2.5%, and a Shore A hardness of 75–83. In this project, testing such as tensile strength, hardness test, morphological analysis of fracture surface, water absorption test, thermal decomposition analysis, thermal aging, process torque, curling and shrinkage was conducted to determine the best replacement percentage of plasticized PVC by reclaimed NBR. Application of rNBR into this compound will reduce the need to use virgin PVC and provide more valuable application or market use for reclaimed NBR. Findings from this work shows that, optimum plasticized PVC/rNBR blend which fulfils these requirements is plasticized PVC/rNBR blends with ratio of 80/20. This blend exhibits 5.25 MPa ultimate tensile strength, 107.20% elongation at break, 2.4276% water absorption, and 75.5 Shore A hardness.